2009
DOI: 10.1111/j.1471-8847.2008.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The International Dimensions of Neuroethics

Abstract: Neuroethics, in its modern form, investigates the impact of brain science in four basic dimensions: the self, social policy, practice and discourse. In this study, we analyzed a set of 461 peer-reviewed articles with neuroethics content, published by authors from 32 countries. We analyzed the data for:(1) trends in the development of international neuroethics over time, and (2) how challenges at the intersection of ethics and neuroscience are viewed in countries that are considered developed by International M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 12 publications
(8 reference statements)
3
14
0
Order By: Relevance
“…Hence, from a wider perspective of a technology-driven understanding of neuroethics this finding was expected. This result follows a trend that has been reported by Lombera and Illes (2009), who equally found that neuroethics research primarily centers in high-income countries as defined by the World Bank. However, in comparison to their investigation into the international dimensions of neuroscience from a quantitative perspective on the published research output, more contributions from countries like France, the Netherlands, Israel or Switzerland would have been expected.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Hence, from a wider perspective of a technology-driven understanding of neuroethics this finding was expected. This result follows a trend that has been reported by Lombera and Illes (2009), who equally found that neuroethics research primarily centers in high-income countries as defined by the World Bank. However, in comparison to their investigation into the international dimensions of neuroscience from a quantitative perspective on the published research output, more contributions from countries like France, the Netherlands, Israel or Switzerland would have been expected.…”
Section: Resultssupporting
confidence: 88%
“…This finding is consistent with those of Lombera and Illes (2009), who showed a dominance of publications on the “ethics and practice of brain science.” However, it does not mirror observations of Gooray and Fergusson (Gooray and Ferguson, 2013), who rank literature on moral philosophy and moral psychology as the second most abundant issue in neuroethics after issues in cognitive enhancement. This last opposing result, however, is very likely due to the use of different data-sets.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As Illes et al [11] suggest, neuroethics can be broadly defined as concerned with ethical, legal and social policy implications of neuroscience, and with aspects of neuroscience research itself. Lombera et al [12] define neuroethics as a discipline that aligns the exploration and discovery of neurobiological knowledge with human value systems and intersects with biomedical ethics, being concerned with ethical, legal, and social implications of neuroscience. Gazzaniga [13] characterizes neuroethics in a general manner, as the examination of how we want to deal with the social issues of disease, normality, mortality, lifestyle, and philosophy of living informed by our understanding of underlying brain mechanisms.…”
Section: Conceptual Frameworkmentioning
confidence: 99%